2017
DOI: 10.1007/s00396-017-4014-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid and phospholipid interactions useful for repaired articular cartilage surfaces—a mini review toward tribological surgical adjuvants

Abstract: This mini review is focused on the emerging nexus between the medical device and pharmaceutical industries toward the treatment of damaged articular cartilage. The physical rationale of hyaluronic acid and phospholipid preparations as tribological surgical adjuvants for repaired articular cartilage surfaces is explored, with directions for possible new research which have arisen due to the therapeutic advance of the physiochemical scalpel. Because synovial joint lubrication regimes become dysfunctional at arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
(46 reference statements)
0
36
0
Order By: Relevance
“…Hyaluronic acid and phosphatidylcholine are important components of the lubricating molecular layer in joint synovial systems. Furthermore, due to their extensive profiles of biocompatibility and their recognized therapeutic applications, these molecules have been recognized as essential candidates for tribological surgical adjuvant design [33].…”
Section: Hyaluronic Acid/phosphatidylcholine Bilayer Interactionsmentioning
confidence: 99%
“…Hyaluronic acid and phosphatidylcholine are important components of the lubricating molecular layer in joint synovial systems. Furthermore, due to their extensive profiles of biocompatibility and their recognized therapeutic applications, these molecules have been recognized as essential candidates for tribological surgical adjuvant design [33].…”
Section: Hyaluronic Acid/phosphatidylcholine Bilayer Interactionsmentioning
confidence: 99%
“…For instance, it has been reported that addition of hyaluronan and phospholipids together is more effective in alleviating joint disease symptoms than any of these two components alone. 9 In model experiments hyaluronan-phospholipid mixtures have also shown synergies, 10,11 and the importance of hyaluronan-phospholipid association structures for repaired articular cartilage surfaces 12 and for lubrication of hip implants 13 has been stressed. Different aspects of biolubrication and biomimetic lubrication have been the topic of several valuable reviews that we recommend to the interested reader.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the lipid peak weakening is that the damage treatments may have exposed the lipids embedded within the articular surface and allowed them to dissolve in the PBS solution. The lack of surface-active lipid bilayer is seen on damaged AC surface , Jung et al 2017. Furthermore, the EDTA present within PBS solution during storage could have caused the lipids to dissolve.…”
Section: Discussionmentioning
confidence: 99%